Peran Pelayanan Sosial Panti Yauma Palmerah Dalam Pendidikan Anak Yatim Dan Dhuafa - Inayah Umnihannie; Wa Ode Asmawati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Education is a fundamental human right, yet numerous children, particularly orphans and underprivileged youth, still lack access to proper education. Ministry of Education and Culture data for the 2022/2023 academic year highlights a significant dropout rate across various education levels, primarily due to economic factors. To assist orphans and underprivileged individuals, Yauma Palmerah Orphanage operates several social service programs devoted to education. This study examines social services in education and the factors that facilitate or hinder these services. Field research with a descriptive qualitative analysis approach was conducted, selecting five informants through purposive sampling. The findings demonstrate that Panti Yauma Palmerah has a significant role in providing social services for the educational needs of underprivileged orphans. Yauma Orphanage provides social services to meet the educational needs of its foster children, including the development of academic potential, psychological potential, and social potential. Supporting and inhibiting factors are also present. Supporting factors include the creativity of administrators and teachers, the motivation of children and donors, appreciation, and outside teaching staff.